Persepsi Konsumen dan Strategi Pemasaran dalam Pengembangan Agroindustri Tiwul Instan Produksi KWT Kenanga Ponorogo - Agnes Ayu Rahmawati; Joni Murti Mulyo Aji (Master of Management Diponegoro University, 2022)
KWT Kenanga is an agro-industry driver made from cassava in Sidoharjo Village by processing cassava into instant tiwul. However, the number of production and sales of instant tiwul product